Factors influencing the decision to receive total knee replacement among patients with severe knee osteoarthritis under universal health insurance coverage - Cheng-Chi Wang; Kui-Chou Huang; Ming-Chou Ku; Chien-Chou Pan; Cheng-Pu Hsieh; Ing-Lin Chang; Chung-Yuh Tzeng; Chao-Ping Chen; Yung-Heng Lee; Yen-Jen Chen; Yi-Shiun Tsai; Pei-Tseng Kung; et al. (Scientific Reports)
Abstract This study aimed to investigate the factors influencing the decision of patients with severe knee osteoarthritis, who are covered by universal health insurance, to undergo total knee replacement (TKR) surgery, as recommended by orthopedic physicians. A questionnaire survey was used to collect participants’ demographics, socio-economic status, medical history, baseline Oxford Knee Score (OKS), and EuroQol-5 Dimension Questionnaire (EQ-5D). We included 704 patients with severe knee osteoarthritis, of which 487 underwent TKR (surgery group), while 217 did not (non-surgery group). Descriptive statistics was used to compare the characteristics of patients in the two groups, while logistic regression identified the factors influencing patients’ choice for TKR. Patients aged 75–79 or older were less likely to undergo TKR; those with poorer OKS (OR = 0.83, 95% CI: 0.79–0.86) and lower EQ-5D VAS scores (OR = 0.97, 95% CI: 0.95–0.99) were more likely to undergo TKR. Household income did not significantly affect the decision of the patients to undergo surgery. In conclusion, for patients with severe knee osteoarthritis, the impact of joint discomfort on function and quality of life is the primary factor influencing their decision to undergo TKR, while economic factors do not have a significant impact under the provision of universal health insurance coverage.